Ecological Investigations Pertaining to Aquatic Vegetation in two Ponds Situated within the Municipal Jurisdiction of Sidhi (Madhya Pradesh), India - Salim , Mohammad; Prajapati , I. P.; Prajapati , Prabha (Recent Trends in the Study of Botanical Research Volume - 1, 2023)
The paper focuses on a study conducted during the 2017-2018 period in two Nagarpalika areas within the Sidhi district of Madhya Pradesh. The research explores aquatic weeds and their ecological characteristics. A total of 36 weed species were identified across the wetlands. Notably, species such as Eichhornia crassipes, Ipomoea aquatica, Typha angustifolia, and Hydrilla verticillata were consistently present in both ponds throughout the entire year.